Neurologic adverse events of cancer immunotherapy - Marcelo Houat de Brito (Arquivos de Neuro-Psiquiatria)
ABSTRACT Cancer immunotherapy encompasses a wide range of treatment modalities that harness the anti-tumor effects of the immune system and have revolutionized oncological treatment in recent years, with approval for its use in more and more cancers. However, it is not without side effects. Several neurological adverse events have been recognized associated with immune checkpoint inhibitors (ICI) and chimeric antigen receptor (CAR) T-cell therapy, the two main classes of cancer immunotherapy. With the increase in the prevalence of oncological diseases and this type of therapy, it is improbable that neurologists, oncologists, hematologists, and other healthcare professionals who deal with cancer patients will not encounter this type of neurologic complication in their practice in the following years. This article aims to review the epidemiology, clinical manifestations, diagnosis, and management of neurological complications associated with ICI and CAR T-cell therapy.